1980
DOI: 10.1038/clpt.1980.156
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear pharmacokinetic models for 5-fluorouracil in man: Intravenous and intraperitoneal routes

Abstract: A two-compartment physiologic pharmacokinetic model has been developed for 5-fluorouracil (5FU). This model, which incorporates saturable whole body clearance, satisfactorily predicts disappearance kinetics after an intravenous bolus and steady-state levels during constant intravenous infusions. A half-saturating concentration (KM) of 15 microM was determined by comparison of model simulations with literature data. Both hepatic and extrahepatic elimination can be inferred for 5FU, but the exact anatomic or com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(41 citation statements)
references
References 0 publications
5
36
0
Order By: Relevance
“…As reported previously, there was a significant relationship noted between the 5-FU dose and AUC (Milano et al, 1988). Several studies have reported the pharmacokinetics of 5-FU to be nonlinear with increasing 5-FU dose (Christophidis et al, 1978;McDermott et al, 1982;Collins et al, 1980). As reported by others (Erlichman et al, 1986), we found the pharmacokinetics of 5-FU following continuous infusion to be linear and clearance to be unchanged with increased 5-FU doses within a 2 fold range (550-1069 mg m2day-' x 5).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As reported previously, there was a significant relationship noted between the 5-FU dose and AUC (Milano et al, 1988). Several studies have reported the pharmacokinetics of 5-FU to be nonlinear with increasing 5-FU dose (Christophidis et al, 1978;McDermott et al, 1982;Collins et al, 1980). As reported by others (Erlichman et al, 1986), we found the pharmacokinetics of 5-FU following continuous infusion to be linear and clearance to be unchanged with increased 5-FU doses within a 2 fold range (550-1069 mg m2day-' x 5).…”
Section: Discussionsupporting
confidence: 56%
“…Several studies following intravenous bolus or oral administration of 5-FU have suggested the systemic clearance of 5-FU is saturable (nonlinear) with increasing 5-FU dose (Christophidis et al, 1978;McDermott et al, 1982;Collins et al, 1980). In contrast, steady-state concentrations of 5-FU have been observed to increase linearly with dose following continuously administered 5-FU (Erlichman et al, 1986).…”
mentioning
confidence: 99%
“…For the calculation of the bioavailability a constant clearance has been assumed. However, as pointed out earlier it is known that the clearance of 5-FU is saturable (Collins et al, 1980). We chose a relatively high dose rate of 5-FU (250 mg /1.5 h) to increase the chance to be well above the detection limit also in case of poor s.c. absorption.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…administration assuming a constant clearance. The 5-FU clearance has been described to be half-saturated (Km) at a concentration of 15 LM (1.95 tg ml-') (Collins et al, 1980 Discussion 5-FU is an important component in the treatment of a variety of solid tumours. In colorectal cancer 5-day high-dose or prolonged (several weeks) continuous low-dose infusion have shown higher response rates and were better tolerated than standard 5-day monthly bolus regimen (Seifert et al, 1975;Lokich et al, 1989).…”
Section: Kinetic Analysismentioning
confidence: 99%
“…When given by the intraperitoneal route, floxuridine (FUDR) showed an appreciable catabolic clearance mainly by the liver 16,17 and greater potency compared with 5-FU. 18 Hepatic artery infusion (HAI) of FUDR may induce hepatic fibrosis, but intra-abdominal fibrosis associated with IP FUDR has not been previously described.…”
mentioning
confidence: 99%